Obstacles of banking insurance and its affection analysis of financial ratios in insurance companies (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Find the impediments Activity vital and important, but focuses a bancassurance activity, diagnosis and its impact on the financial ratios indicators for insurance companies. The researcher has adopted in his research on several financial ratios used to analyze the financial performance of a (relative profitability, liquidity ratio and the ratio of solvency) of the company Iraqi insurance for a period of one year (2009) to a year (2015), based on the annual reports and financial statements (balance sheet revealed income), financial statements for insurance premiums for banks research sample of this research has addressed several topics of theoretical and practical body through which the researcher obstacles to banking and insurance experiences of countries around the bancassuranceAnd also dealt with the subject of financial ratio analysis to insurance companies, and the last side to ensure the practical and analytical framework. The research was based on the premise that the president of the obstacles bancassurance and statistically significant effect on financial ratios for insurance companies, there is a significant statistical significance between the internal and external obstacles in the financial ratios effect The research aims to identify the concept of bancassurance, and to identify the most important obstacles to the potential activities that may hinder its implementation and to know the extent of their impact in the performance of financial ratios for insurance companies and then develop ways to analyze and manipulate the way of the desired objectives, concluded the researcher during the study that the obstacles bancassurance affect impact morally and statistically on financial ratios for insurance companies and prove the hypotheses developed by the researcher, the researcher has come to several conclusions the most important((Despite the success of the banking activity insurance financial sector, but there are constraints limiting the growth and development affect the financial performance represented by financial ratios for the concerned institutions (insurance companies and banks), the lack of a clear strategy for securing the banking whether the insurance companies or the banks, this activity including group insurance to customers of banks) were not covered so far and individual documents. and per capita income has a direct impact on the growth and the spread and development of this vital activity)). As for the most important recommendations of the research are: ((development and establishment of a special department to secure banking in the Iraqi insurance companies. Dependence on technological and technical development of the insurance and banking.